The high tide club - Andrews, Mary Kay, 1954- (St. Martin's Press, 2018)
"When ninety-nine-year-old heiress Josephine Bettendorf Warrick summons Brooke Trappnell to Talisa Island, her 20,000 acre remote barrier island home, Brooke is puzzled. Everybody in the South has heard about the eccentric millionaire mistress of Talisa, but Brooke has never met her. Josephine's cryptic note says she wants to discuss an important legal matter ... Over a few meetings, the ailing Josephine spins a tale of old friendships, secrets, betrayal and a long-unsolved murder. She tells Brooke she is hiring her for two reasons: to protect her island and legacy from those who would despoil her land, and secondly, to help her make amends with the heirs of the long dead women who were her closest friends, the girls of The High Tide Club"--Amazon.com.
Keywords: Female friendship -- Fiction; Love stories